2017
DOI: 10.1038/s41467-017-00962-1
|View full text |Cite
|
Sign up to set email alerts
|

High grade serous ovarian carcinomas originate in the fallopian tube

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the most frequent type of ovarian cancer and has a poor outcome. It has been proposed that fallopian tube cancers may be precursors of HGSOC but evolutionary evidence for this hypothesis has been limited. Here, we perform whole-exome sequence and copy number analyses of laser capture microdissected fallopian tube lesions (p53 signatures, serous tubal intraepithelial carcinomas (STICs), and fallopian tube carcinomas), ovarian cancers, and metastases from nine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
490
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(552 citation statements)
references
References 47 publications
15
490
1
3
Order By: Relevance
“…Furthermore, while ovarian involvement in HGSC is typically bilateral, as is common in metastasis to a paired organ, tubal involvement is unilateral in the majority of cases 12. These observations are supported by detailed molecular analysis demonstrating shared TP53 mutation between STIC and HGSC, and that the majority of mutational and copy abnormalities seen in HGSC are also identified in accompanying STIC 13. Clonal evolution studies demonstrate the same result14 15 but also show that, in advanced cases, intraepithelial tubal metastasis can produce lesions indistinguishable from STIC, further demonstrating the futility of studying advanced HGSC to answer questions about its origin.…”
Section: Resultsmentioning
confidence: 71%
“…Furthermore, while ovarian involvement in HGSC is typically bilateral, as is common in metastasis to a paired organ, tubal involvement is unilateral in the majority of cases 12. These observations are supported by detailed molecular analysis demonstrating shared TP53 mutation between STIC and HGSC, and that the majority of mutational and copy abnormalities seen in HGSC are also identified in accompanying STIC 13. Clonal evolution studies demonstrate the same result14 15 but also show that, in advanced cases, intraepithelial tubal metastasis can produce lesions indistinguishable from STIC, further demonstrating the futility of studying advanced HGSC to answer questions about its origin.…”
Section: Resultsmentioning
confidence: 71%
“…To the best of our knowledge, this is the largest study performing whole‐exome mutational landscape analysis on p53 signatures, dormant STICs and proliferative STICs from cancer‐free women, although a recent study has also analyzed a few such lesions . We found that, compared with tubal lesions associated with ovarian cancer, these incidental tubal lesions have fewer somatic mutations or allelic imbalances, indicative of their earlier occurrence in the tumor evolution timeline.…”
Section: Discussionmentioning
confidence: 81%
“…It is now believed that most serous ovarian cancers develop in the fallopian tube and can spread to the peritoneal cavity early in the course of the disease, which may make early detection more difficult 31. Therefore, the development of techniques involving brush cytology of the fallopian tube provides another potential screening avenue.…”
Section: Ca125 Screenmentioning
confidence: 99%